Oral Health and Environmentally Related Factors Associated with General Health and Quality of Life - Isola, Gaetano; Patini, Romeo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The relationship of oral disease to overall disease is certainly not a new concept. For centuries, the role of oral infection and inflammation in contributing to diseases elsewhere in the body has been studied and reported. During the last few decades, a series of intriguing reports from many countries have increased the current interest in the role of oral health and disease in contributing to general health and systemic conditions. Is it possible that oral and periodontal disease is a risk factor for cardiovascular and other systemic diseases? Since this question was first posed, a phenomenal body of work has been directed at understanding how oral periodontal disease might affect distant sites and organs and, thus, have an effect on overall health. Recent studies of the human microbiome using DNA sequencing technologies have revealed new insights into the possible mechanisms that help to explain how oral infections can occur in distinct sites such as atheromas, the colon, and reproductive tissues.